The immunological barriers to xenotransplantation. Issue 4 (October 2015) - Vadori, M.; Cozzi, E.
Abstract The availability of cells, tissues and organs from a non‐human species such as the pig could, at least in theory, meet the demand of organs necessary for clinical transplantation. At this stage, the important goal of getting over the first year of survival has been reported for both cellular and solid organ xenotransplantation in relevant preclinical primate models. In addition, xenotransplantation is already in the clinic as shown by the broad use of animal‐derived medical devices, such as bioprosthetic heart valves and biological materials used for surgical tissue repair. At this stage, however, prior to starting a wide‐scale clinical application of xenotransplantation of viable cells and organs, the important obstacle represented by the humoral immune response will need to be overcome. Likewise, the barriers posed by the activation of the innate immune system and coagulative pathway will have to be controlled. As far as xenogeneic nonviable xenografts, increasing evidence suggests that considerable immune reactions, mediated by both innate and adaptive immunity, take place and influence the long‐term outcome of xenogeneic materials in patients, possibly precluding the use of bioprosthetic heart valves in young individuals. In this context, the present article provides an overview of current knowledge on the immune processes following xenotransplantation and on the possible therapeutic interventions to overcome the immunological drawbacks involved in xenotransplantation.